Saudi Arabia EFL university students’ voice on challenges and solution in learning academic writing - Alharbi, Mohammed Abdullah (Universitas Pendidikan Indonesia, 2019)
The present study aims to investigate the difficulties faced by 74 English as a foreign language (EFL) undergraduate students in developing a well-written paragraph in academic writing by designing a writing course based on the students’ voices. The self-report survey (5-point Likert scale) was used as the pre- and post-questionnaire, and pre- and the post-tests task was used to track students’ writing improvement before and after taking a writing course. Pre-questionnaire and pre-tests showed that participants had difficulties in using the mechanics of writing (punctuation, spelling, grammar, topic sentences, and supporting sentences). The majority of the students’ responses in the post-survey shows that they believed their writing improved and encountered fewer difficulties in writing as compared to their views in the pre-questionnaire. The result of the post-tests indicates improvements in students’ writing samples. The study concludes that EFL writing courses should be designed on the basis of challenges faced by the students in order to get the best outcome from the course.